Acoustic Crystallization of 2D Colloidal Crystals - Menath, Johannes; Mohammadi, Reza; Grauer, Jens Christian; Deters, Claudius; Böhm, Maike; Liebchen, Benno; Janssen, Liesbeth M.C.; Löwen, Hartmut; Vogel, Nicolas (Advanced Materials, 2023)
2D colloidal crystallization provides a simple strategy to produce defined nanostructure arrays over macroscopic areas. Regularity and long-range order of such crystals is essential to ensure functionality, but difficult to achieve in self-assembling systems. Here, a simple loudspeaker setup for the acoustic crystallization of 2D colloidal crystals (ACDC) of polystyrene, microgels, and core–shell particles at liquid interfaces is introduced. This setup anneals an interfacial colloidal monolayer and affords an increase in average grain size by almost two orders of magnitude. The order is characterized via the structural color of the colloidal crystal, the acoustic annealing process is optimized via the frequency and the amplitude of the applied sound wave, and its efficiency is rationalized via the surface coverage-dependent interactions within the interfacial colloidal monolayer. Computer simulations show that multiple rearrangement mechanisms at different length scales, from the local motion around voids to grain boundary movements via consecutive particle rotations around common centers, collude to remove defects. The experimentally simple ACDC process, paired with the demonstrated applicability toward complex particle systems, provides access to highly defined nanostructure arrays for a wide range of research communitie
Keywords: structural color; monolayers; self-assembly; colloids; crystallization